The Analysis of Students Difficulty in Essay Writing Course - Aulia, Lailani Sarafina; Rizal, David (Journal of English Education Forum (JEEF), 2024)
This study investigates the difficulties faced by university students in writing essays, particularly in the context of English education in Indonesia. The research identified key challenges such as limited vocabulary, anxiety, time constraints, and difficulty in organizing ideas. Through a quantitative approach that included an online distributed survey, this study collected data on students' experiences and perceptions of their writing skills. The results showed that many students experienced difficulties in various aspects of writing, including grammar and coherence, which often led to a lack of confidence and motivation. The findings highlight the need for better teaching strategies to improve students' writing skills. Recommendations include providing intensive guidance during the writing process, implementing project-based learning, and utilizing technology to support learning. In addition, fostering a supportive environment where students can freely explore topics of interest is essential to motivate them to write effectively. Overall, this study underscores the importance of overcoming skill-based and psychological barriers to improve academic writing proficiency among students in the digital age.